Why was Slavery not Abolished in 1798? : Humanity and Human Rights in the Batavian Revolution - Alkemade, Dirk (BMGN - Low Countries Historical Review, 2024)
The ‘problem of slavery’ was an important moral issue in the eighteenth-century Dutch enlightened press, but the increase in publications on this topic did not lead to any serious attempts to abolish the practice. This seemed to change during the Batavian Revolution, when abolition was briefly discussed in parliament. This article analyses Dutch anti-slavery debates, especially within the context of the Dutch revolutionary parliament in 1797. It shows that the humanitarian sentiments in these debates did not automatically lead to support for abolition. Only radical representatives argued for the abolishment of slavery on the grounds of ‘human rights’. On this basis, this article posits a hermeneutical distinction between anti-slavery and abolition. Het ‘slavernijprobleem’ was een belangrijke morele kwestie in de achttiende-eeuwse Nederlandse verlichte pers. Toch leidde de toename van het aantal publicaties over dit onderwerp niet tot serieuze pogingen om deze praktijk af te schaffen. Dit leek te veranderen tijdens de Bataafse Revolutie, toen de afschaffing kortstondig in het parlement werd besproken. Dit artikel analyseert de Nederlandse anti slavernijdebatten, vooral binnen de context van het Nederlandse revolutionaire parlement in 1797. Het laat zien dat de menslievende sentimenten in deze debatten niet automatisch leidden tot steun voor de afschaffing. Alleen radicale volksvertegenwoordigers bepleitten de noodzaak van afschaffing op basis van ‘mensenrechten’. Dit artikel poneert daarom een hermeneutisch onderscheid tussen anti-slavernij en afschaffing.